Peutz-Jeghers Syndrome in Children: High Recurrence Rate in Short-term Follow-up - Tomoaki Taguchi; Sachiyo Suita; Shohei Taguchi; Shinji Tanaka (Asian Journal of Surgery, 2003)
We have managed four cases of Peutz-Jeghers syndrome (PJS) in children. Fathers of three of these patients had PJS. There was also a family history of cancer in three cases, with pancreatic cancer in a father, colonic and laryngeal cancers in a grandfather, and hepatic and gastric cancers in a grandmother. It is presumed that in each of the cases, the largest polyp was responsible for initial symptoms. Preoperative examination revealed additional small polyps in the whole alimentary tract except for the oesophagus. Patients underwent laparotomy to remove the largest polyps and subsequent intraoperative endoscopic polypectomy for other small polyps, to minimize intestinal resection. Follow-up gastrointestinal examinations, including upper gastrointestinal series, small intestinal contrast study, and barium enema, were repeated about once a year. Three of four cases showed recurrent small intestinal polyps, and one required a second laparotomy because of recurrent abdominal pain. In conclusion, patients with PJS occurring in childhood have a strong hereditary family history of cancer and a high incidence of recurrence. Careful follow-up examination is mandatory for the gastrointestinal tract, as well as other solid organs that are susceptible to malignant change, throughout a patient's life.